Plan de negocio para la creación de un centro de convivencia espiritual de danza y teatro en el cantón El Empalme, año 2014 - Romero Cevallos, Ana Cristina (2014)
Currently in city the Empalme no Spiritual Living Centers Dance Theatre where young worship and thank God for his mercy through movement and gifts received on earth. Dancing is part of the attitude of Ecuador, the social rate goes to dance to highlight moments and through the body symbolize relationships with the self and between individuals. Taking these points into consideration trying to solve a spiritual need, developing a business plan for the creation of a Center for Spiritual Living dance theatre in city the Empalme 2014, in order to meet this demand satisfying and the youth of the county. The center will be called spiritual coexistence Education Center Dance Theatre "Soldiers of Christ", its location will be in city El Empalme in Av. Amazona and Duale, offering the services of Hebrew worship and joy dances, rhythmic dance of different music genres and robotic dance rhythm or comic theater, musical theater, mime, mimes and awareness talks about faith in Jesus Christ the son of God. Advertising is the conduct by the radius (Ondateca). An investment of $ 7,470.75 will be required, with a 5% contingency it will be funded at 80.31% against a claim which would be held at the National Development Bank (BNF), with an interest of 15% 5 year term and 19.69% by equity. The NPV equals $ 42,375.30 being positive value indicating that the business plan is profitable the TIR is equal to 156%, with a higher rate that is used for calculations. The payback will be in 8 months and 19 days, which is another affirmation of the viability of the business plan